Figure 60. Various Forms of Snow. Figure 61. Dissection of Ice by the Solar Rays - Cazin, Achille (The Phenomena and Laws of Heat, 1869)
Two illustrations from page 166 of the 1869 volume The Phenomena and Laws of Heat by Achille Cazin. Figure 60 depicts a magnified view of various forms of snow. Figure 61 depicts the dissection of ice by solar rays.
Keywords: Heat; Heat--Conduction; Evaporation; Snow; Scientific illustration; Scientific apparatus and instruments